Peran Gaya Kepemimpinan Trilogi Dalam Meningkatkan Budaya Inovatif: Dengan Peran Mediasi Knowledge Sharing Climate (Studi Pada Dosen Perguruan Tinggi Swasta Di Wilayah Kopertis V Diy) - Prayekti, Prayekti (Universitas Muhammadiyah Yogyakarta, 2018)
Innovation Culture as the strength of a business enterprise in the face of intense competition, so it is seen as a very important variable. This study aims to explore the role of Trilogy Leadership and Knowledge Sharing Climate in improving the Culture of Innovation. The research object is lecturer at private university in Kopertis V area. The tool used to test the hypothesis using Structural Equation Modeling (SEM). The results of the analysis of the proposed hypothesis are all accepted, where the Leadership Trilogy directly or indirectly have a significant positive effect on the Culture of Innovation. With the proven role of Trilogy Leadership to the Culture of Innovation either directly or through Knowledge Sharing Climate, it will become an interesting reference and very important for academics and practitioners related to the style of Trilogy Leadership.